JEJAK PARSI DI NUSANTARA: Interplay antara Agama dan Budaya - Yusni Saby (Sharia and Law Faculty, 2017)
The relationship of Nusantara, in particular Aceh, to the Persian is not new. It has been done since long time ago. In fact, the relationship is much earlier than with the Arabian Peninsula. This is due to the following reasons. Geographically, Persian, as compared to Arabian Peninsula is closer to Nusantara; Persian has experienced growth of knowledge, including in sailing activities; and Persian is also surrounded by the sea at the South and the West which enable them to travel to Nusantara earlier than Arabian Peninsula. This relationship has brought implication to the Nusantara in religious life and culture. This article aims to explore the influence of Persian to the Nusantara in particular Aceh which are manifested in religious life and culture.